1995
DOI: 10.2307/1941211
|View full text |Cite
|
Sign up to set email alerts
|

Socioecology of a Terrestrial Salamander: Juveniles Enter Adult Territories During Stressful Foraging Periods

Abstract: When adults of a species defend feeding territories, juveniles may benefit from access to those territories during periods when prey decline between territorial spaces. Adults may either deny or allow such access, thus impacting the foraging success of the juveniles. We examined a dense population of the terrestrial red—backed salamander (Plethodon cinereus) in which male and female adults hold territories (cover objects on the forest floor that act as patches of moisture and prey during rainless periods) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…For terrestrial amphibians, higher amounts of precipitation increase humidity on the forest floor and underneath moisture-retaining cover (assuming this is not counteracted by increased temperatures), thus facilitating more opportunities to forage [129][130][131]. Above average rainfall in one year may increase the terrestrial prey base for adult females, which may then translate into greater reproductive success (through more "fit" offspring) in the subsequent year.…”
Section: Food Availabilitymentioning
confidence: 99%
“…For terrestrial amphibians, higher amounts of precipitation increase humidity on the forest floor and underneath moisture-retaining cover (assuming this is not counteracted by increased temperatures), thus facilitating more opportunities to forage [129][130][131]. Above average rainfall in one year may increase the terrestrial prey base for adult females, which may then translate into greater reproductive success (through more "fit" offspring) in the subsequent year.…”
Section: Food Availabilitymentioning
confidence: 99%
“…Red-backed salamanders can be the most abundant vertebrate in a forest in terms of biomass [Burton and Likens, 1975], forming dense populations at some study sites [e.g. Jaeger et al, 1995]. A life history study of P. cinereus in Maryland suggested that it takes 2 years for eggs to develop, and mature females probably deposit eggs in moist nest sites on land every other year [Sayler, 1966].…”
Section: Introductionmentioning
confidence: 99%
“…This information about the scent producer includes gender [Martin et al, 2000], familiarity vs. unfamiliarity [Jaeger, 1981;Gillette et al, 2000b], quality of diet [Walls et al, 1989;Gabor and Jaeger, 1995;Karuzas et al, 2004], kinship [Forester and Anders 2000], and whether or not they had other mating partners [Gillette et al, 2000a]. Adults of both sexes and juveniles can detect the information in pheromones [Horne and Jaeger, 1988;Jaeger et al, 1995], and the vomeronasal system is specifi cally implicated in pheromone detection through a behavior called nose-tapping. Salamanders nose-tap each other [touch the bases of nasolabial grooves which transport odorants preferentially to the vomeronasal organ; 1989] and the substrate, including feces.…”
mentioning
confidence: 99%